2017
DOI: 10.7759/cureus.1166
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Stress Cardiomyopathy During COPD Exacerbation: Are Beta-adrenergic Agonists Only to Blame?

Abstract: Takotsubo cardiomyopathy (TCM) is a variant of stress-induced cardiomyopathy, characterized by transient left ventricular dysfunction that may be associated with emotional or physical triggers. We present the case of a 51-year-old Caucasian female with severe chronic obstructive pulmonary disease (COPD) who presented with syncope and was found to have her second lifetime episode of stress-induced cardiomyopathy. Eight months prior, she had been admitted with a COPD exacerbation and was found to have left ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…It has been widely suggested that a bronchogenic sub type of TCM exists[3]. Although not as common, there have been some reported cases of TCM in the setting of COPD or asthma[4,5]. Some authors even estimate that pulmonary pathologies are suspected to be found in as high as 44% of TCM cases[6], thus justifying the creation of a separate classification as a bronchogenic subtype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely suggested that a bronchogenic sub type of TCM exists[3]. Although not as common, there have been some reported cases of TCM in the setting of COPD or asthma[4,5]. Some authors even estimate that pulmonary pathologies are suspected to be found in as high as 44% of TCM cases[6], thus justifying the creation of a separate classification as a bronchogenic subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors even estimate that pulmonary pathologies are suspected to be found in as high as 44% of TCM cases[6], thus justifying the creation of a separate classification as a bronchogenic subtype. The disproportionate predominance of sympathetic activity during a COPD exacerbation has been noted as a possible trigger for TCM[4]. Rajwani et al[3] described 5 specific cases of bronchogenic TCM and noted some distinguishing features.…”
Section: Discussionmentioning
confidence: 99%
“…Takotsubo cardiomyopathy has been found to be associated with physical and emotional triggers. Some of these stressors include pheochromocytoma, myocarditis, psychiatric illnesses, prolonged QT syndromes, COPD exacerbations, albuterol, hyperthyroidism, seizure disorders, electroconvulsive therapy, acute brain injury, and sepsis [6][7][8][9][10][11][12][13][14][15]. For this reason, the syndrome has also been referred to as "stress-induced" cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…“Bronchogenic TTS” has been proposed as a specific form of TTS that occurs during severe acute dyspnea in asthma or COPD, with atypical presentation [1012]. Recurrent TTS in COPD seems to be exceptionally rare since only a handful of clinical cases have previously been reported in the literature [13, 14]. Here, we present a unique case of frequently recurrent TTS during COPD exacerbation with at least 4 different episodes of TTS.…”
Section: Introductionmentioning
confidence: 94%